2011
DOI: 10.1136/bjophthalmol-2011-300360
|View full text |Cite
|
Sign up to set email alerts
|

Residual corneal stroma in big-bubble deep anterior lamellar keratoplasty: a histological study in eye-bank corneas

Abstract: It should no longer be assumed that big-bubble DALK, where the bubble has a white margin, routinely bares DM. True baring of DM may only occur with the less commonly seen clear margin bubble.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…McKee et al. () described it as ‘residual stroma’ and Jester et al. () in an informative and balanced editorial which partly related to our paper (Dua et al.…”
Section: Discussionsupporting
confidence: 58%
“…McKee et al. () described it as ‘residual stroma’ and Jester et al. () in an informative and balanced editorial which partly related to our paper (Dua et al.…”
Section: Discussionsupporting
confidence: 58%
“…Despite the initial controversy (McKee et al. ; Schlötzer‐Schrehardt et al. ), the lack of airspaces in PDL and its impervious (to air) nature; the concentration of elastin fibres in PDL (Lewis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that the cleavage plane in the BB that forms with the white margin is actually intrastromal 7,8 and that the cleavage plane in clear margin bubbles was between the stroma and DM and not intra-DM. 7,9 Other authors have named the white margin bubble with an intrastromal dissection plane as a type 1 bubble and the clear margin bubble as a type 2 bubble. 10 The aim of this study was to retrospectively review preoperative factors and intraoperative complications of BB DALK in light of the 2 different bubble types.…”
mentioning
confidence: 99%